El Teatro Campesino theater in the Chicano movement - Broyles-González, Yolanda 1949- (Univ. of Texas Press, 1994)
Writing within contemporary cultural studies theory, Broyles-Gonzalez sheds light on class, gender, race, and cultural issues, showing how they traverse and inform the Chicana/o performance aesthetic embodied by El Teatro Campesino. Her work situates the Teatro within working-class Mexican performance history, the Chicano movement, gender relations, and contemporary attempts to mainstream